Danielle Steel's Safe harbour - Gilbert, Melissa 1964-; Johnson, Brad 1959-; Staab, Rebecca 1961-; Grodnik, Dan; Swensen, Edithe; Corcoran, William; Steele, Danielle 1947-; Newman, Joey 1976- (D'Concorde Recording Corp., 2007)
Ophélie is a grieving young widow, Matt is a heartbroken artist. Both feel as though they have lost everything until they find each other.